Oral condition of patients admitted in Intensive Care Units (Research, Society and Development, 2021)
Objective: To identify the oral condition of patients admitted to intensive care units. Methodology: This is a retrospective observational study using secondary data from medical records of patients admitted to the intensive care units of a high complexity charitable hospital in the city of Recife, attended by the Hospital Dentistry team from March 2019 to February 2020. Results: The sample involved a total of 1831 patients, with an average age of 67.63 years, 50.8% of whom were male. Neurological (19.9%) and respiratory (18.8%) diseases were responsible for the highest admission rates. The main oral alterations evidenced were: tartar (27.2%), dental fracture (17.1%), injury / infection (14.4%) and dry lip / mouth (10%). Conclusion: It is concluded that tartar was the most frequent oral alteration in the evaluated patients, observed with greater number in patients with neurological and respiratory diseases. The presence of infection / injury in the oral cavity was diagnosed at a higher rate in cancer patients.